Design and development of a twin disc test rig for the study of squeal noise from the wheel – rail interface - Omasta, Milan; Navrátil, Václav; Gabriel, Tomáš; Galas, Radovan; Klapka, Milan (Serbian Academic Center, 2022)
The aim of this paper is to present the design of the twin-disc test rig for the study of the wheel-squeal phenomena. This test rig utilizes a dynamic model of the track-train interaction and uses real train wheel for a more realistic representation of the emitted noise. This twin-disc test rig is intended for research into the mechanisms of the wheel squeal noise formation and for the development and validation of a prediction model. In particular, the influence of weather conditions and the presence of various friction layers in the contact will be addressed.

The aim of this paper is to present the design of the twin-disc test rig for the study of the wheel-squeal phenomena. This test rig utilizes a dynamic model of the track-train interaction and uses real train wheel for a more realistic representation of the emitted noise. This twin-disc test rig is intended for research into the mechanisms of the wheel squeal noise formation and for the development and validation of a prediction model. In particular, the influence of weather conditions and the presence of various friction layers in the contact will be addressed.
Design and development of a twin disc test rig for the study of squeal noise from the wheel – rail interface
Keywords: adhesion characteristic; dynamic model; twin-disc; wheel squeal noise; wheel-rail contact; adhesion characteristic; dynamic model; twin-disc; wheel squeal noise; wheel-rail contact